ANALISIS KUALITAS PELAYANAN WISATA SEJARAH KOMPLEK MASJID BANTEN LAMA-BENTENG SUROSOWAN DITINJAU DARI KARAKTERISTIK PENGUNGJUNG DALAM IMPLEMENTASI KEBIJAKAN PARIWISATA - Sonny Sonny (Prima Center Indonesia, 2016)
Tourism policy implementation Mosque Complex History of Banten Lama - Benteng Surosowan. Business and visitors Mosque Complex History of Banten Lama - Benteng Surosowan consist of various heterogeneous characteristics, it can bring up the problems of the quality level of service to visitors, the Service Quality History Analysis of Complex Mosque of Banten Lama - Benteng Surosowan Seen From Visitor Characteristics In Implementation Tourism Policy. This research was conducted at the site of Masjid Complex History of Banten Lama - Benteng Surosowan, by taking samples at the visitors, with a technique that is used is